2013
DOI: 10.1111/cas.12220
|View full text |Cite
|
Sign up to set email alerts
|

Identification of integrin α3 as a molecular marker of cells undergoing epithelial–mesenchymal transition and of cancer cells with aggressive phenotypes

Abstract: Epithelial-mesenchymal transition (EMT) is a crucial event in wound healing, tissue repair, and cancer progression in adult tissues. Transforming growth factor (TGF)-b induces EMT in mouse epithelial cells. During prolonged treatment, TGF-b successively induces myofibroblastic differentiation with increased expression of myofibroblast marker proteins, including smooth muscle a actin and calponin. We recently showed that fibroblast growth factor-2 prevented myofibroblastic differentiation induced by TGF-b, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…ESRPs are also expressed at low levels in the basal‐like subtype, and repressed by direct binding of δEF1/SIP1 to their promoter regions, similar to the repression of E‐cadherin by δEF1/SIP1. Recently, we found that ITGA3 was highly expressed in the basal‐like subtype, and that ERK inhibitor downregulated expression of ITGA3 . When ITGA3 is functionally blocked by neutralizing antibodies or its expression is reduced by ERK inhibitor or its specific siRNA, invasive properties are significantly repressed in breast cancer cells and glioma cells .…”
Section: Epithelial–mesenchymal Transition In Cancermentioning
confidence: 99%
“…ESRPs are also expressed at low levels in the basal‐like subtype, and repressed by direct binding of δEF1/SIP1 to their promoter regions, similar to the repression of E‐cadherin by δEF1/SIP1. Recently, we found that ITGA3 was highly expressed in the basal‐like subtype, and that ERK inhibitor downregulated expression of ITGA3 . When ITGA3 is functionally blocked by neutralizing antibodies or its expression is reduced by ERK inhibitor or its specific siRNA, invasive properties are significantly repressed in breast cancer cells and glioma cells .…”
Section: Epithelial–mesenchymal Transition In Cancermentioning
confidence: 99%
“…Integrins act as transmembrane scaffolds that connect the ECM to the actin cytoskeletal system; they also function as mediators of mechanotransduction and regulate cell proliferation, migration, invasion, and survival [Desgrosellier and Cheresh, ]. Upregulation of β3 integrin in response to TGF‐β is critical for initiation of the EMT process [Parvani et al, ; Shirakihara et al, ].…”
mentioning
confidence: 99%
“…The protein expression of E‐cadherin increased 2.3‐fold ( P < 0.05) in ZEB2‐induced shETS1‐DLD1 cells compared to shpLKO.1‐DLD1 cells (Figure B). A previous report showed that SNAIL1 expression in DLD1 cells resulted in the acquisition of invasive properties along with apparent repression of E‐cadherin but without an increase in the expression of N‐cadherin, fibronectin, and vimentin . In line with this, we could not detect vimentin expression in ZEB2‐induced DLD1 cells, and we explored the downregulation of the EMT regulator SNAIL1 and a mesenchymal marker integrin α3 in response to ETS1 knockdown in these cells .…”
Section: Resultsmentioning
confidence: 58%